Assessment of Anxiety during COVID-19 Pandemic among General Population of India - Anamika Gautam; Poonam Ahlawat; Shikha Sharma Thapa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction -The coronavirus COVID-19 illness makes a very unpredictable future the main psychologicaleffect is elevated rates of anxiety, because of pandemic and the lockdown.Aim -The aimed of the study was to Assess the level of anxiety during COVID-19 among general populationin India.Methodology -A Snowball sampling technique was used to collect the samples from different state andunion territory of India. Total 829 participants respond and enrolled themselves in the study. Participants inthe study belong to 27 states or union territories of India and majority of them are from Delhi.Result-Most of the Participant in the study was female (54%), graduate (51%), age between 18-28 (60%)and Hindu (89.3%). Half of the participant were having minimal anxiety (57.1%) nearly one fourth ofthe participant were having Mild anxiety (28.5%) and least number of participants were having Moderateanxiety (11.0%) and Severe anxiety (3.5%).There was no significant association of Anxiety scores withSocio-demographic variable except place of stay, suffering from any health problem and During lockdownperiod time spent in watching news related to corona (COVID-19) on mobile, laptop, television etc.Conclusion-The study concluded the outbreak of coronavirus disease 2019 (COVID-19) Cause anxietyamong the people. Understanding the risk to yourself and people you care about can make an outbreak lessadverse effect on mental and physical health of the people